2015
DOI: 10.1038/mp.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

HCN channels are a novel therapeutic target for cognitive dysfunction in Neurofibromatosis type 1

Abstract: Cognitive impairments are a major clinical feature of the common neurogenetic disease neurofibromatosis type 1 (NF1). Previous studies have demonstrated that increased neuronal inhibition underlies the learning deficits in NF1, however, the molecular mechanism underlying this cell-type specificity has remained unknown. Here, we identify an interneuron-specific attenuation of hyperpolarization-activated cyclic nucleotide-gated (HCN) current as the cause for increased inhibition in Nf1 mutants. Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 55 publications
9
95
4
1
Order By: Relevance
“…Treatment with the HCN channel agonist lamotrigine during adulthood rescued the cognitive deficits in two different Nf1 mouse models, thereby establishing an important function of HCN channels in mediating the NF1 phenotype. In contrast, HCN function is unaffected in HRas G12V/G12V mice 25 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Treatment with the HCN channel agonist lamotrigine during adulthood rescued the cognitive deficits in two different Nf1 mouse models, thereby establishing an important function of HCN channels in mediating the NF1 phenotype. In contrast, HCN function is unaffected in HRas G12V/G12V mice 25 .…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, in order to investigate if a similar mechanism might be present in HRas G12V/G12V mice, we recorded spontaneous miniature inhibitory postsynaptic currents (mIPSCs) in the presence of depolarizing levels of extracellular potassium (increased from 2.5 to 12.5 mM KCl), as previously shown for Nf1 mice 24, 25 . As expected, high extracellular potassium (12.5 mM) resulted in a significantly increased frequency of mIPSCs in both HRas G12V/G12V and WT mice (frequency: F 1,49  = 22.28, P  < 0.05, amplitude: F 1,49  = 1.21, P  = 0.28; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This drug is an agonist of the hyperpolarization-activated, cyclic-nucleotide-gated channel 1 (HCN1) that is compromised predominantly in inhibitory interneurons of an animal model of the disorder. Lamotrigine has been demonstrated to correct the electrophysiological and the cognitive deficits in NF1 knockout mice (Omrani et al, 2015).…”
Section: Therapeutic Trials Based On Gabaergic Treatmentmentioning
confidence: 99%
“…Recently, Omrani and colleagues showed that Nf1 mutants with the specific deletion of exon 9a recapitulate the phenotypes of the Nf1 +/-mice, including spatial learning and memory deficits in the water maze, increased GABAergic inhibitory synaptic transmission, and impaired hippocampal LTP (Omrani, van der Vaart, Mientjes, van Woerden, Hojjati, Li et al, 2015). In addition, Omrani et al identified hyperpolarization-activated cyclic nucleotide-gated channel 1 (HCN1) as a novel interacting partner of NF1 and showed that hyperpolarization-activated cation current was reduced selectively in parvalbumin (PV)-expressing inhibitory neurons in Nf1 9a-/9a-mice (Omrani et al, 2015). Moreover, augmenting the HCN current by lamotrigine treatment rescued the electrophysiological and behavioral deficits in both Nf1 9a-/9a-and Nf1 -/-mice (Omrani et al, 2015).…”
Section: Rui Costa Found That Inhibitory Synaptic Transmission Is Enhmentioning
confidence: 99%
“…In addition, Omrani et al identified hyperpolarization-activated cyclic nucleotide-gated channel 1 (HCN1) as a novel interacting partner of NF1 and showed that hyperpolarization-activated cation current was reduced selectively in parvalbumin (PV)-expressing inhibitory neurons in Nf1 9a-/9a-mice (Omrani et al, 2015). Moreover, augmenting the HCN current by lamotrigine treatment rescued the electrophysiological and behavioral deficits in both Nf1 9a-/9a-and Nf1 -/-mice (Omrani et al, 2015). However, decreases in HCN1-current in Nf1 9a-/9a-mice might be independent from the upregulation of RAS-MAPK signaling.…”
Section: Rui Costa Found That Inhibitory Synaptic Transmission Is Enhmentioning
confidence: 99%